Synthesis, Crystal Structure and Antibacterial Properties of N-(2-Hydroxy-1-naphthalidene)-4-aminoantipyrine - GUO, FENG; BI, CAI-FENG; FAN, YU-HUA; XIAO, YAN; HE, XUE-TAO; XU, JIA-KUN (Asian Journal of Chemistry, 2010)
The structral features of Schiff base (N-(2-hydroxy-1- naphthalidene)-4-aminoantipyrine) formed by the interaction of 4-aminoantipyrine and 2-hydroxy-1-naphthaldehyde with the formula C22H19N3O2 has been determined by X-ray diffraction method and elemental analysis. The crystal belongs to orthorhomic system with space group P2(1)2(1) 2(1), a = 8.8170(18) Å, b = 14.605(3) Å, c = 14.734(3) Å, V = 1897.3(7) Å-3, Z = 4, R1 = 0.0414, wR2 = 0.1063, F(000) = 752, respectively for 2306 observed reflections. In addition, the compound has been tested for its antibacterial active. The compound showed antibacterial activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and had no antibacterial activity against Bacillus subtilis.